FUNGSIONALISASI MASJID NABAWI DAN RELEVANSINYA TERHADAP MASJID MODERN DALAM PANDANGAN PROF. DR. KH. NASARUDDIN UMAR, MA - Rahmat, Ihsan; Nurbaiti, Ayu Soraya; Kusuma, Wira Hadi (Jurnal Manajemen Dakwah, 2025)
In early Islam, the Prophet Muhammad peace be upon him (PBUH) established the Nabawi mosque as a multifunctional space capable of managing the various affairs of the people. The mosque functions have undergone a shift, with a greater emphasis on worship, resulting in the diminution of other roles. This article will explore the insights of Prof. Nasaruddin Umar, MA, regarding the functionalization of the Nabawi Mosque and its relevance to modern mosques. Our research method involved a comprehensive bibliographic approach, encompassing the following phases: defining the research focus, collecting primary and secondary data, coding and analyzing the data, presenting the findings, and drawing conclusions. The study's findings indicate that Umar's perspective is founded on the assertion that mosques function as the nucleus of Muslim civilization. Nabawi Mosque fulfills eight primary functions: worship, education and skills development, interfaith information and communication, health services, arts and culture, governance (public policy and management), social and philanthropic activities, and emergency disaster response. Governance and disaster management unfortunately are no longer found, but economic and tourism functions emerge in contemporary mosques. Consequently, future researchers must document best practices in mosque functionalization, particularly in disaster emergency governance and management.